Trademark Spaces and Trademark Law’s Secret Step Zero - Lemley, Mark A.; McKenna, Mark P. (Revista Amagis Jurídica, 2024)
When is a design just a design, and when is it a trademark? Over the last several decades, courts have developed a clear framework for evaluating the distinctiveness of certain unconventional marks, especially those typically conceived of as “trade dress.” The Supreme Court has drawn a line between product packaging, on the one hand, and product design, on the other. Packaging features are treated just like any other potential trademark in the sense that we protect them automatically if they are inherently distinctive, and we require evidence of secondary meaning if they aren’t. Product design is different. Like color, it is incapable of being inherently distinctive and can be protected only when it has acquired secondary meaning. There’s just one problem with this fundamental rule: It isn’t true. Or at least, it isn’t the whole truth. As we show in this Article, sometimes courts and the trademark Office don’t recognize features like logos as being part of a product’s design, and as a result, they ignore the categorization system and evaluate the claimed features for inherent istinctiveness. Something similar happens with certain product packaging features, except in reverse. In other words, courts are engaged in a previously unrecognized “step zero” before they classify trade dress features and apply the normal rules of distinctiveness for product packaging and product configuration. In that largely implicit step, courts and trademark examiners make their own judgments about the role of that feature, and particularly whether they believe consumers are likely to regard those features as trademarks. While courts and the Trademark Office have been slow to articulate rules for step zero – or even to acknowledge that it exists – we show in this article that in practice they are recognizing what we call “trademark spaces”: locations that consumers are likely to assume are serving as trademarks. When they apply this implicit step zero, courts and the Trademark Office frequently treat the location of a claimed feature on the product or package as an important determinant of trademark status. As we describe in detail, some locations are special. Use in those spaces goes a long way to convincing a court or trademark examiner that the design is a trademark. The recognition of trademark spaces offers a way to rationalize the step zero analysis and to begin thinking more systematically about the relationship between distinctiveness and use as a mark. Courts can and should evaluate use in a trademark space as part of the broader step zero inquiry. But they should do so explicitly and based on evidence, not instinct. Bringing step zero out into the open will help us better understand when and why consumers react to certain designs as trademarks. And it will pave the way for us to reject claims to own things that either do not or should not function as trademarks.